Views on Child Rearing in the Study of Imam Ghazaliʼs Legacy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
During the years of independence, broad opportunities opening up for the comprehensive economic, political and spiritual development of our society. Today, the use of the teachings and advice of our ancestors to ensure the spiritual and moral education of young people has a special pedagogical value. In this article, the spiritual end pedagogical heritage created by Imam Ghazali is important in educating the younger generation. After all, spiritual heritage, pedagogical views, ideas, didactic works created by him serve to form the younger generation as a fully mature, well-rounded person, to provide them with proper education and upbringing. Because, in the pedagogical heritage of lmam Ghazali, the issues of human decency, morality, faith, conscience, freedom, family, and child upbringing are theoretically substantiated.